Promoting Eco-Pesantren: Islamic Boarding Schools' Role in Sustainable Facility Development and Environmental Management - Widiastuti, Mega Ayu; Ernawati, Rita (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This study examines sustainable facility development strategies in Islamic boarding schools (pesantren) via a comparative analysis of Pondok Pesantren Assalafi Al Fithrah and Pondok Pesantren Al-Amanah Junwangi. The research utilizes qualitative approaches such as facility documentation, direct observation, user surveys, and management interviews carried out from August to September 2022. Analysis identifies eight essential characteristics for sustainable facility development: water conservation, energy management, waste management, health concerns, disaster readiness, sustainable site management, and environmentally friendly materials. Results indicate that effective implementation necessitates both passive and active environmental solutions. Passive strategies in architectural design demonstrate efficacy through natural ventilation systems, ideal building orientation, and the incorporation of green spaces, whereas active strategies, such as waste management systems and energy conservation programs, exhibit inconsistent levels of performance. The research delineates principal obstacles to implementation, such as deficiencies in technical skills, expenses associated with infrastructure development, spatial limits, and issues in operational management. The study presents an optimization methodology that highlights integrated resource monitoring systems, centralized waste management facilities, improved passive design elements, and reinforced community participation initiatives. These findings offer a thorough framework for the creation of eco-friendly pesantren facilities, enhancing both theoretical comprehension and practical implementation strategies for Islamic educational institutions aiming for environmental sustainability objectives. Future research prospects lie in the development of quantitative assessment methodologies for facility performance and the enhancement of stakeholder engagement in environmental management initiatives.